The Effect Of Brand Image, Product Quality, And Lifestyle On Purchase Decisions For Xiaomi Smartwatches In Bandar Lampung - Gabriel Frederick Faska Prasetyo; Aida Sari; Nuzul Inas Nabila (International Journal of Business and Quality Research, 2026)
The development of wearable technology, particularly smartwatches, has continued to increase along with people’s need for devices that can support daily activities, health, and modern lifestyles. Xiaomi has become one of the widely used smartwatch brands because it offers affordable prices and competitive features. However, the large number of brand choices has made consumers more selective in making purchase decisions. This study aims to determine the influence of brand image, product quality, and lifestyle on the purchase decision of Xiaomi smartwatch products in Bandar Lampung City. This research uses a quantitative approach with primary data obtained through questionnaires distributed to 190 Xiaomi smartwatch users. The sampling technique used is purposive sampling, while the data were analyzed using multiple linear regression with the assistance of SPSS. The results show that brand image, product quality, and lifestyle have a positive and significant influence on purchase decisions. The coefficient of determination indicates that brand image, product quality, and lifestyle are able to explain 24.3% of purchase decisions, while the remaining percentage is influenced by other factors outside this study. Therefore, Xiaomi needs to strengthen its brand image, improve product quality, and adjust its products to consumers’ lifestyles in order to increase purchase decisions.